Energy dissipation characteristics of additively manufactured CNT/ABS nanocomposites. Issue 3 (14th January 2020) - Gardea, Frank; Cole, Daniel P.; Glaz, Bryan; Riddick, Jaret C.
Abstract : Purpose: This study aims to discuss the effect of carbon nanotubes (CNTs) on the mechanical properties of acrylonitrile–butadiene–styrene (ABS) composites fabricated by additive manufacturing (AM). Insight into the energy-dissipation mechanisms introduced and/or enhanced by the addition of CNTs is presented in this study. Design/methodology/approach: ABS/CNT filaments were fabricated with different concentrations of CNTs. Using a fused deposition modeling approach, unidirectional specimens were printed using a MakerBot Replicator 2X (MakerBot Industries, Brooklyn, NY, USA). Specimens were tested under static and dynamic conditions, with the loading coinciding with the printing direction, to determine elastic modulus, strength and viscoelastic properties. Findings: A CNT reinforcing effect is evident in a 37 per cent increase in elastic modulus. Likewise, the strength of the composite increases by up to 30 per cent with an increase in weight fraction of CNTs. At low dynamic strain amplitudes (0.05 per cent), a correlation between dissipated strain energy of the butadiene phase and strength of the composite is found such that less dissipation, from constraint of the butadiene particles by the CNTs, leads to higher strength of the composite. At higher dynamic strains, the presence of a high concentration of CNT leads to increased energy dissipation, with a maximum measured value of 24 per cent higher loss factor compared to baseline specimens. Because the trend of the composite behavior is similar (with a higher absolute value) to that of neat ABS, this study's results indicate that well-established polymer/CNT dissipation mechanisms (such as stick-slip) are not significant, but that the CNTs amplify the dissipation of the ABS matrix by formation of crazes through stress concentrations. Originality/value: This study provides knowledge of the dissipation behavior in additively manufactured ABS/CNT composites and provides insight into the expansion to new printable materials for dynamics applications.